Principals Supervision Strategy in Improving Student Learning Achievement at SD Negeri Medangharuman - Diah Nurlatipah; Ika Rostika; Laelatul Mutmainah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study aims to analyze the supervision strategies implemented by the principal at SD Negeri Medangharuman in an effort to improve student learning achievement. Using a descriptive qualitative approach, this study explores various types of supervision carried out, namely academic, administrative, and personal supervision. The results of the study show that academic supervision carried out through classroom observation and constructive feedback improves the quality of teacher teaching and student learning outcomes. Administrative supervision involving the management of work programs and transparent evaluations also contributes to more structured learning management. In addition, personal supervision that pays attention to the welfare of teachers helps create motivation in teaching. However, there are several challenges faced by school principals, such as time constraints, resistance from teachers, and low parental participation. This research suggests the importance of better time management, more open relationships with teachers, and increased parental involvement in supporting student achievement.